2013
DOI: 10.1002/jclp.21946
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Demand Characteristics and Social Desirability on Clients’ Ratings of the Therapeutic Alliance

Abstract: The results indicate that alliance scores were not inflated due to the presence of a therapist or knowing that the scores would be observed by the therapist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 58 publications
4
42
0
1
Order By: Relevance
“…[ The therapist ] and I respect each other). The WAI‐SR sees widespread use and has solid evidence of generating reliable and valid scores in psychotherapy (Hatcher & Gillaspy, ; Reese et al., ). For the current study, coefficient alpha for the WAI‐SR was .91.…”
Section: Methodsmentioning
confidence: 99%
“…[ The therapist ] and I respect each other). The WAI‐SR sees widespread use and has solid evidence of generating reliable and valid scores in psychotherapy (Hatcher & Gillaspy, ; Reese et al., ). For the current study, coefficient alpha for the WAI‐SR was .91.…”
Section: Methodsmentioning
confidence: 99%
“…Gillaspy and Murphy () reported the average internal consistency of SRS scores across five studies equaled .92 (range .88 –.96). SRS scores also exhibit moderate evidence for concurrent validity with longer alliance measures; r =.48 with the Helping Alliance Questionnaire–II (Duncan et al., ), r = .63 with the Working Alliance Inventory (WAI; Campbell & Hemsley, ), and r = .65 with the WAI–Short Revised (Reese et al., ). The predictive validity of SRS scores has been supported by two studies.…”
Section: The Partners For Change Outcome Management Systemmentioning
confidence: 99%
“…Seven studies examined the effect of SD in self‐reports of treatment variables and outcomes, and in most of them SD correlated negatively with certain undesirable self‐reports such as psychiatric symptoms or drug addiction severity and correlated positively with desirable characteristics such as parental happiness or treatment attendance. On the contrary, two studies found a negligible effect of SD on clinical outcomes such as therapeutic alliance (Reese et al., ) and self‐management of chronic disease (Nolte, Elsworth, & Osborne, ).…”
Section: Resultsmentioning
confidence: 99%